2021
DOI: 10.1212/con.0000000000000965
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Headache and Other Trigeminal Autonomic Cephalalgias

Abstract: PURPOSE OF REVIEWThe trigeminal autonomic cephalalgias (TACs) are relatively rare, but they represent a distinct set of syndromes that are important to recognize. Despite their unique features, TACs often go undiagnosed or misdiagnosed for several years, leading to unnecessary pain and suffering. A significant proportion of TAC presentations may have secondary causes.RECENT FINDINGSThe underlying pathophysiology of TACs is likely rooted in hypothalamic dysfunction and derangements in the interplay of circuitry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 55 publications
0
26
1
1
Order By: Relevance
“…SUNCT can also be confused with trigeminal neuralgia as they share a similar duration, location, and cutaneous triggers over the area of pain. However, unlike trigeminal neuralgia, SUNCT has strong ipsilateral cranial autonomic features and no refractory period after cutaneous triggering [ 2 ]. For secondary headaches, several systematic reviews of case series have identified causes of SUNCT-like headaches including pituitary tumors (the most common cause), other neoplasms (carcinoid, epidermoid, meningioma, pilocytic astrocytoma, lung adenocarcinoma), vascular (aneurysm, cavernous sinus dural fistula, compression of the trigeminal nerve by the superior or anterior inferior cerebellar artery), inflammatory/infectious (multiple sclerosis, viral meningitis), or an orbital cyst [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SUNCT can also be confused with trigeminal neuralgia as they share a similar duration, location, and cutaneous triggers over the area of pain. However, unlike trigeminal neuralgia, SUNCT has strong ipsilateral cranial autonomic features and no refractory period after cutaneous triggering [ 2 ]. For secondary headaches, several systematic reviews of case series have identified causes of SUNCT-like headaches including pituitary tumors (the most common cause), other neoplasms (carcinoid, epidermoid, meningioma, pilocytic astrocytoma, lung adenocarcinoma), vascular (aneurysm, cavernous sinus dural fistula, compression of the trigeminal nerve by the superior or anterior inferior cerebellar artery), inflammatory/infectious (multiple sclerosis, viral meningitis), or an orbital cyst [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TACs consist of five headache disorders: cluster headache, paroxysmal hemicrania, short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT), short-lasting unilateral neuralgiform headache attacks with cranial autonomic symptoms (SUNA), and hemicrania continua. These conditions differ in their attack duration, attack frequency, and treatments [ 2 ]. SUNCT, the disease discussed in this case, is officially characterized by 1) at least 20 attacks, 2) moderate or severe pain in the temple and/or one or more distributions of the trigeminal nerve lasting between 1 second and 10 minutes, 3) ipsilateral autonomic features which must include both conjunctival injection and lacrimation, 4) at least one attack most days unless in remission, and 5) not better accounted for by another diagnosis [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may experience a single attack, recurrent attacks with pain-free interictal periods, or a sawtooth pattern background pain with superimposed stabs. 1,2 13 (1) Conjunctival injection and/or lacrimation, (2) Nasal congestion and/or rhinorrhea, (3) Eyelid edema, (4) Forehead and facial sweating, (5) Forehead and facial flushing, (6) Sensation of fullness in the ear, (7) Miosis and/or ptosis both intra and extra-axial (vascular lesion, tumor, or bony abnormalities). Multiple Myeloma (MM) with central nervous system involvement (CNS MM) most commonly presents with visual changes (36%), radiculopathy (27%), headache (25%), confusion (21%), dizziness (7%), and seizures (6%).…”
Section: Introductionmentioning
confidence: 99%
“…Adapted from 13 (1) Conjunctival injection and/or lacrimation, (2) Nasal congestion and/or rhinorrhea, (3) Eyelid edema, (4) Forehead and facial sweating, (5) Forehead and facial flushing, (6) Sensation of fullness in the ear, (7) Miosis and/or ptosis…”
Section: Introductionmentioning
confidence: 99%